Penerapan Metode Protoype Dalam Perancangan Sistem Pendukung Keputusan Pemilihan Pemasok Berbasis Web Dengan Metode Simple Additive Weighting (SAW) - Davit Hermawan (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Analysis and design of this decision support system aim to address issues surrounding the selection of the best supplier which is a problem at BAZNAS West Java Province. Supplier selection is one of the important things in purchasing activities for institutions, where purchasing activities are activities that have important value for the company. In making decisions to select suppliers, decision makers need analytical tools that enable them to solve complex problems so that the decisions taken are of a higher quality. In making this decision using the Simple Additive Weighting (SAW) method. SAW is one of the algorithms for making decisions. The SAW method is commonly known as an algorithm with a weighted addition method. So that BAZNAS of West Java Province can determine the best supplier appropriately. The system development methodology used to build this system is the Prototype method. With this method, developers and customers can interact with each other during the system creation process.